A little black number: Undressing transformation from student to pattern maker - Cavanagh, M. (South African Journal of Higher Education, 2018)
Frequently, there is a gap between students’ knowing, being and doing. This is significant in vocations where students must “become” discipline professionals, transforming their identities as they begin to understand the what, how and why of their profession. As learning cannot happen in isolation, it is crucial that staff support this metamorphosis. Tinto argues that the first year is the most important time for this support, when integration into the university is beginning. This project used action research to facilitate students’ journey to becoming pattern makers. Tinto’s framework underpinned a scaffolded approach: Expectations were clearly stipulated throughout the project: students were to design and construct a pattern for and ultimately sew a little black dress. Support was given through lecturer guidance, consultations and tutor assistance. Feedback was given weekly in time for students to correct work before beginning the next step. In a practical project it is inevitable that students are involved in the learning process. In the case of this project, they needed to use pattern making to link Creative Design and Garment Technology together. A focus group was conducted with students to understand if and how they experienced the transformation of becoming. By creating clear expectations, support, timely feedback and involvement, it was possible to facilitate the transformation less painfully than previous years. The implication for student well-being in higher education is that students who feel supported are more likely to succeed. This project is still challenging for students as it allows them to rise to higher expectations.